ABDUL GTIAFFAR· Department of Fibre Technology, University of Agriculture, Faisalabad, Pakistan (Biological Sciences - PJSIR, 2022)
In this study, cotton sliver characteristics were compared among different speeds of extra roller fixed under takerinand a high speed conventional card. Modified card with extra roller running at 150 rpm in clockwise motion produceddominating results over all other settings in respect to card and drawing sliver characteristics. Moreover, maximum wasteextraction with minimum card web neps were also achieved at this speed.